Penanaman Pendidikan Islam Pada Generasi Milenial - Siti Nadhifa Imtinan; Aninda Triazya Rinjani; Destina Inggrid Diani; Yulia Damayanti; Zahidah Nurul Kamilah (-, 2022)
The rapid development of technology greatly affects human life, especially the lives of millennials. The purpose of this study is to determine the role of Islamic da'wah in the millennial era along with the rapid development of technology and the increasing prevalence of juvenile delinquency. The types and methods used in this research are quantitative research types and methods. Participants in this study consisted of students (13.7%), students (70.6%), teachers (9.9%), and the general public (5.9%). The data collection technique was using a questionnaire via Google Form to find out how far the participants' understanding was related to the topic to be studied. Analysis of the data used in this study in the form of tables and pie charts based on the questionnaire survey that has been conducted. The results of this study indicate that increasing public understanding of the importance of da'wah is one solution in dealing with the high rate of juvenile delinquency. Although there is no visible physical evidence, the results of the respondents show that there is public concern for the reduction in juvenile delinquency which can be overcome by da'wah. To achieve success in overcoming as an effort to minimize the occurrence of juvenile delinquency, it is highly recommended that we can apply this da'wah on an ongoing basis.